Study on LTE Service Requirements and Evolution of Service Network Towards Mobile Internet Network - Hua Ren; Zheng Wang; Jun Luo; Jiayu Bi; Ping Yang (Dianxin kexue)
With the development of mobile internet network technique，mobile internet network service has become the fastest growing and the 1argest potentia1 field in the market. As is known to a11，the vigorous development of mobile internet network service has close connection with the mature of telecom operators’ 3G network. According to the development trend of mobile internet services，service requirements of LTE were analyzed and some solutions about undertaking existing services，as we11 as evolution direction in architecture and function about service network in LTE were given.